Integration of Fiqh al-Bi’ah and Indigenous Environmental Practices: A Study of the Pa’jukukang Tradition in Bantaeng Regency - Tahir, Muhammad; Maloko, M Thahir; Talli, Abdul Halim (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
This research aims to conduct a critical study of the environmental impacts caused by the implementation of the pa’jukukan tradition from an environmental jurisprudence perspective. This type of research is classified as qualitative field research using descriptive analysis methods and syar’i approach methods. The results of the research show that the implementation of the pa’jukukang tradition consists of four stages, namely appasulu pangngajai, akkawaru, Kalau’u ri pa’jukukang, angnganre ta’bala’na and angnganre Raja’na. It contains positive and negative impacts on the environment. From the perspective of Environmental Jurisprudence, the implementation of the pa’jukukang tradition contains environmental ethical principles which consist of the principles of spirituality; ihtiram wa hizh al-bi’a, istikhlaf wa al-amanah, al-mizan, al-’adl wa al-ihsān; al-maṣlaḥah li al-‘amm, lā tufsidū fī al-arḍ wa lā tabżآr; and sustainability. Therefore, it is necessary to mainstream environmental jurisprudence in the implementation of the pa’jukukang tradition.